Clinical course of COVID-19 infection in elderly patient with melanoma on nivolumab. (July 2020) - Yekedüz, Emre; Dursun, Bengü; Aydın, Güle Ç; Yazgan, Satı C; Öztürk, Halis H; Azap, Alpay; Utkan, Güngör; Ürün, Yüksel
Outbreak of the new type coronavirus infection, known as coronavirus infection 2019 (COVID-19), has begun in December 2019, in Wuhan, China. As of today, 3 April 2020, 972, 640 people affected and 50, 325 people died from Severe Acute Respiratory Syndrome-Coronavirus 2. There is not any standard treatment for coronavirus infection 2019; however, there are promising data for hydroxychloroquine and some anti-retroviral drugs. Programmed death-1 (PD-1)/programmed death ligand-1 (PDL-1) pathway is an important target for the cancer immunotherapy. However, there is a robust pre-clinical and clinical data regarding inhibitor effect of this pathway on the acute or chronic viral infections. Thus, blockade of this pathway may lead to an anti-viral effect and decrease viral load. Here, we report the clinical course of coronavirus infection 2019 infection of a patient in whom older aged, having multiple co-morbidities, and taking nivolumab for metastatic malignant melanoma. In contrast to her older age, comorbidities, and cancer diagnosis, she was in a good condition, and there was also no pneumonia finding. We think that this good clinical course of coronavirus infection 2019 infection may be related to blockade of PD-1/PDL-1 pathway with nivolumab. It is impossible to say that blockade of PD-1/PDL-1pathway is a treatment option for COVID-19; however, we want to share our experience.